É o meu parecer : a censura política à música de protesto nos anos de chumbo do regime militar do Brasil (1969-1974) - Souza, Amilton Justo de (2010)
This Master Dissertation is linked to the Research Line: Regional History , of Post-Graduation Program in History of the Paraíba Federal University, which has Historical Culture and History as its Area of Concentration. Our research have as objective to analyze above all, the use of the political censorship on protest music during the called shot years of the military dictatorship in Brazil. With this intent we have focused mainly on the judgments elaborated by the censors themselves, between 1969 and 1974, during the censure practice, to justify the vetos on the protest songs, censureds for having political protests opposite the political regime in vigour, established in Brazil by the militaries with the stroke of 1964. Therefore, we have tried to demonstrate that, besides the moral censorship which held in the country during the military dictatorship and that had been applied since the mid 40 s, also during that military regime themselves, there was a political censorship on the Brazilian popular music, wich acted with more vigour during the shot years and mainly on the protest music, which directioned more its contestations for the political situation in Brazil at that moment. Besides, no refuse wich happened in that period themselves a moral censorship on the popular music made in Brazil. Though, we have tried to show too that there was, at certain moments, an interconnection between the political and moral motivations for the censorship of determinates songs.